Immunogenicity of Monoclonal Antibodies and the Potential Use of HLA Haplotypes to Predict Vulnerable Patients - Mosch, Romy; Guchelaar, Henk-Jan (Frontiers in Immunology, 2022)
The use of monoclonal antibodies (mAbs) in the clinic has successfully expanded to treatment of cancer, viral infections, inflammations, and other indications. However, some of the classes of mAbs that are used in the clinic show the formation of anti-drug antibodies (ADAs) leading to loss of efficacy. This review describes ADA formation for the various mAbs, and its clinical effect. Lastly, this review considers the use of HLA-haplotypes as biomarkers to predict vulnerability of patients sensitive to formation of ADAs.